2021
DOI: 10.5483/bmbrep.2021.54.6.050
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis exacerbates the progression of fatty liver disease via CD36-PPARγ pathway

Abstract: Periodontal diseases have been reported to have a multidirectional association with metabolic disorders. We sought to investigate the correlation between periodontitis and diabetes or fatty liver disease using HFD-fed obese mice inoculated with P. gingivalis. Body weight, alveolar bone loss, serological biochemistry, and glucose level were determined to evaluate the pathophysiology of periodontitis and diabetes. For the evaluation of fatty liver disease, hepatic nonalcoholic steatohepatitis (NASH) was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Previous animal studies have mainly focused on the effects of a single periodontal pathogen on NAFLD. 8 , 27 , 28 However, the key pathogenic hypothesis may not fully reveal the complexity of the pathogenesis and interactions between periodontitis and NAFLD. Consequently, a mixed bacterial dysbiosis model related to periodontitis may provide better scientific support than a single-species model and can better simulate actual clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have mainly focused on the effects of a single periodontal pathogen on NAFLD. 8 , 27 , 28 However, the key pathogenic hypothesis may not fully reveal the complexity of the pathogenesis and interactions between periodontitis and NAFLD. Consequently, a mixed bacterial dysbiosis model related to periodontitis may provide better scientific support than a single-species model and can better simulate actual clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low-grade inflammation induced by P. gingivalis infection induces insulin resistance, which affects hepatic glucolipid metabolism and consequently leads to lipid accumulation in hepatocytes. In addition to this, a study by Ahn et al., 2021 found that P. gingivalis induced the progression of nonalcoholic fatty liver disease in high-fat-fed mice by upregulating the CD36-PPARγ axis ( Ahn et al., 2021 ). As one of the important metabolic enzymes in fatty acids, fatty acid translocase 36 (CD36) is widely expressed in various cells (myocytes, monocytes, macrophages, hepatocytes) ( Thanakun et al., 2014 ).…”
Section: Association Of P Gingivalis With Systemic...mentioning
confidence: 98%
“…[80] Ahn et al showed a streamed result with Pg on fatty liver disease in obese mice through the upregulation CD36-PPARγ pathway. [81] Pg-LPS injected via the oral mucosa in the maxilla has been reported to induce the onset of NASH in the liver of rats fed a high-fat diet. [82] In general prevention and/or elimination of Pg infections with dental treatment may have a beneficial effect on NASH.…”
Section: Periodontal Problems and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%